2017
DOI: 10.20944/preprints201703.0077.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of Forest Therapy on Depressive Symptoms among Adults: A Systematic Review

Abstract: This study systematically reviewed forest therapy programs designed to decrease the level of depression among adults and assessed the methodological rigor and scientific evidence quality of existing research studies to guide future studies. This systematic review was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The authors independently screened full-text articles from various databases using the following criteria: (1) intervention studies ass… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…To identify possible criteria that would demonstrate potential bias, we consulted criteria used in prior systematic literature reviews on greenness and human health outcomes [9,10]. We found that some prior criteria (i.e., multiplicity of outcome variables within a single article) did not apply to our unit of examination -that is, analyses rather than articles -and other criteria represented characteristics of potential bias which we had already excluded in our screening process (i.e., expert assessments of "greenness" versus land-cover maps or satellite system assessments).…”
Section: Evaluation Of Possible Biasmentioning
confidence: 99%
“…To identify possible criteria that would demonstrate potential bias, we consulted criteria used in prior systematic literature reviews on greenness and human health outcomes [9,10]. We found that some prior criteria (i.e., multiplicity of outcome variables within a single article) did not apply to our unit of examination -that is, analyses rather than articles -and other criteria represented characteristics of potential bias which we had already excluded in our screening process (i.e., expert assessments of "greenness" versus land-cover maps or satellite system assessments).…”
Section: Evaluation Of Possible Biasmentioning
confidence: 99%